RADT-06. RADIOTHERAPY FOR BRAIN METASTASES FROM THYROID CANCER: A RETROSPECTIVE COHORT STUDY. (12th November 2021) - Blomain, Erik; Berta, Scott; Hug, Nicholas; Giao, Duc; Meola, Antonio; Binkley, Michael; Shahsavari, Nastaran; Desai, Kaniksha; Chang, Steven; Soltys, Scott; Pollom, Erqi
Abstract: PURPOSE/OBJECTIVE(S): Brain metastases from thyroid carcinoma are rare. Although stereotactic radiosurgery (SRS) is a standard of care for patients with brain metastases across many histologies, the current NCCN guidelines do not support a universal role for this modality in thyroid cancer. MATERIALS AND METHODS: Thyroid cancer patients with brain metastases treated with radiotherapy at our institution from 2002-2020 were studied. Cumulative risk of local failure, distant intracranial failure and radiation necrosis were calculated using a competing risk of death analysis and censored at the last imaging follow-up. Overall survival was analyzed using Kaplan-Meier method. Stratified cox regression was used to study per-lesion outcomes. RESULTS: We identified 34 patients with 203 treated brain metastases. 179 (88.2%) lesions were of differentiated histology; the remainder were anaplastic histology. Four patients received whole brain radiotherapy (WBRT) while 30 patients received SRS (SFED 22, interquartile (IQ) range 20-22). Of the patients receiving WBRT, one (25%) had anaplastic histology, and the median number of lesions was 15 (as compared to 2 for SRS). Median follow up among survivors was 32.3 months and median survival was 10.8 months. There were no observed failures (local or distant intracranial) observed at 1 year in the 24 metastases with anaplastic histology, although competing risk of death was high (91.7%). The 1 year cumulative incidences of local failure and distant intracranial failures were 9.8% (95CI 5.7%-13.9%) and 35.0% (95CI 29.0%-41.0%), respectively, in differentiated tumors. 6 (10.2%) of the distant intracranial failures were new cases of leptomeningeal disease. The 1 year risk of radiation necrosis was 15.5%. Of these cases, most were Grade 2 (57.1%); 3 (42.9%) were Grade 4 (there were no Grade 1 or 3 events). CONCLUSION: In the largest known cohort of thyroid cancer brain metastasis patients, radiotherapy and SRS appear to be safe and effective treatment modalities.